Ecovila e permacultura: uma nova forma de viver - Sales, Camilla Barroso (2017)
The general objective of this research is to analyze the relations of Inkiri Piracanga activities with the principles and the permaculture activities practiced in the ecological community. The object of study chosen is Ecovila de Piracanga, especifically the Inkiri Piracanga, located in Maraú, on the southern coast of Bahia. This is a qualitive research, with a case study, in which semi-structured interviews and direct observations of the activities of Inkiri Piracanga and of man-nature relations were carried out during field visits in October 2015 and September 2016. Inkiri Community constitutes the "core community" and Inkiri Piracanga corresponds to the dimensions where it operates within the Ecovila. The social, environmental, economic and spiritual / cultural dimensions of Inkiri Piracanga were analyzed, following the aspects of the Global Ecovillages Network (GEN). life in Piracanga implies experiencing routines and unconventional habits, which suggests reconsiderations and even deconstruction of (unsustainable) patterns of life. permaculture is considered a way of life, a means of achieving spiritual growth through caring for nature. Permaculture is considered a way of life, a means of achieving spiritual growth through caring for nature. Inkiri Piracanga proposes a lifestyle of low environmental impact that drives a new way of living with nature and with people.